PERBEDAAN KEKUATAN PERLEKATAN BAHAN ADHESIF PADA RETAINER CEKAT DENGAN KAWAT MULTISTRAND 0,0195” DAN 0,010” x 0,028” (Eksperimental Laboratoris) - RESTUNING WIDIASIH, 021318066304 (2017)
To determine bond strenght of adhesive on fixed retainer using multistrand wire 0,0195 and multistrand wire 0,010 x 0,028, and to determine Adhesive Remant Index (ARI) score. Materials and methods : Two different multisrand wire were used, 0,0195 and 0,010 x 0,028. To test bond strenght, ten pairs of incisors were embedded in acrylic blocks and divided in two groups. A 15mm lenght of wire was bonded to lingual surface of each pairs incisors using adhesive. A vertical force was apllied to the interdental wire using autograph. To asses Adhesive Remant Index (ARI) score, the failure sites were evaluated by Scanning Electron Microsope. Results : Bond strenght were significantly different between two goups. (p < 0,05). Bond strenght was significantly higher on fixed retainer using multistrand wire 0010 x 0,028. Adhesive Remnant Index (ARI) score were not significantly different between two groups (p > 0,05). Conclusion : Multistrand wires 0,010 x 0,028 are suggested for use in fixed retainer.